Legal Protection For Patients Due To Misdiagnosis In Online Health Service Platforms (Telemedicine) Based On Positive Law In Indonesia - Ronald Suryaprawira; Erikson Sihotang; Ni Ketut Wiratny (Journal of Social Research, 2024)
Health regulations in guaranteeing legal protection for patients regarding misdiagnosis in online health service platforms based on positive law in Indonesia. Protection is contained in the provisions in Article 3 paragraph (2) and paragraph (4), as well as Article 7 of Medical Council Regulation Number 47 of 2020. Prohibitions For doctors who practice medicine via telemedicine, it is regulated in Article 9 of the Medical Council Regulation Number 47 of 2020, which is confirmed by Article 2 of the Minister of Health Regulation Number 20 of 2019. In addition, for Health Facilities providing and requesting consultations, they must register and submit it to the Minister of Health. through the Directorate General of Health Services. Resolving legal disputes between patients and online health service providers if a misdiagnosis occurs can submit a complaint to the Indonesian Medical Discipline Honorary Council in accordance with the provisions of Article 66 of the Medical Practice Law. Resolving legal disputes between patients and online health service providers can settlement through court or outside court.